Opportunities to close wheat yield gaps in Nepal’s Terai: Insights from field surveys, on-farm experiments, and simulation modeling - Devkota Wasti, Mina Kumari; Devkota, Krishna; Paudel, Gokul Prasad; Krupnik, Timothy; James McDonald, Andrew (Elsevier Masson, 2024)
CONTEXT Wheat (Triticum aestivum) is among the most important staple food crops in the lowland Terai region of Nepal. However, national production has not matched the increasing demand. From a South Asian regional perspective, average productivity is low with high spatial and temporal variability.